From imitation to collusion: Long-run learning in a low-information environment - Daniel Friedman; Steffen Huck; Ryan Oprea; Simon Weidenholzer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
We explore the stability of imitation in a 1,200-period experimental Cournot game where subjects do not know the payoff function but see the output quantities and payoffs of each oligopolist after every period. In line with theoretical predictions and previous experimental findings, our oligopolies reach highly competitive levels within 50 periods. However, already after 100 periods quantities start to drop and, eventually fall deep into collusive territory without pausing at the Nash equilibrium. Our results demonstrate how groups of subjects can learn their way out of dysfunctional heuristics, and thus suggest the need for a new theory of how cooperation emerges. – – Wir untersuchen die Stabilität von Imitationsverhalten in einem experimentellen Cournot-Oligopol mit 1.200 Perioden, in denen die Teilnehmer zwar keine Informationen über die Gewinnfunktion haben, aber nach jeder Periode die Output-Mengen und den Gewinn jedes Oligopolisten sehen können. Im Einklang mit theoretischen Vorhersagen und Befunden vorheriger Experimente, erreichen unsere Oligopole hoch-kompetitive Levels innerhalb von 50 Perioden. Aber bereits nach 100 Perioden fangen die Output-Mengen an zu fallen, im weiteren Verlauf sogar bis tief in kollusive Bereiche, ohne am Nash-Gleichgewicht zu pausieren. Unsere Befunde veranschaulichen, wie Gruppen von Personen ihren Weg aus dysfunktionalen Heuristiken heraus finden können, und legen daher die Notwendigkeit einer neuen Theorie über die Entstehung von Kooperation nahe.
Keywords: C73; C91; D43; 330; Cournot oligopoly; imitation; learning dynamics; cooperation